Analisis Pengetahuan Sikap Dan Paparan Media Informasi Terhadap Perilaku Sadari Pada Remaja Putri - Beatrick Rosali Nasta; Riska Wandini; Aprina (Jurnal Kesehatan Panca Bhakti Lampung, 2026)
Background: In 2022, the results of early detection screening for cervical and breast cancer identified 266 positive Visual Inspection with Acetic Acid (VIA) cases, 64 suspected cancer cases, and 159 cases of tumors or breast lumps. Purpose: This study aims to investigate the relationship between knowledge, attitudes, and media exposure concerning SADARI behavior among female adolescents at Pondok Pesantren Diniyah Putri. Method: This study employs a quantitative method with an analytical survey design and a cross-sectional approach. The sample consists of 71 respondents selected using total sampling techniques, with a questionnaire as the data collection instrument. Results: Frequency distribution indicated that 67.6% of respondents exhibited poor behavior, 52.1% had insufficient knowledge, 50.7% had negative attitudes, and 71.8% had low media exposure. Statistical analysis yielded p-values of 0.023, OR = 3.810; p-value = 0.002, OR = 6.565; and p-value = 0.023, OR = 3.972. Conclusion: There is a significant relationship between knowledge, attitudes, and media exposure regarding SADARI behavior.